ACCOUNTING ANALYSIS FOR CRYPTO-ASSETS BASED ON IFRS - I Gede Githa Adhi Pramana; Sekar Mayangsari; Lin Oktris (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
Crypto-asset has begun to develop and is starting to be widely owned by people and institution around the world. Since 2020, government of Indonesia throught Bappebti regulate Crypto-asset transaction as future contract. This is a phenomenon in view of the need for accounting treatment for Crypto-asset transactions. This research attempts to explore transaction characteristic of Crypto-asset with the approach and review of IAS and focus on the accounting treatment for cryptocurrency. The purpose of this study is to conduct a study of accounting for Crypto-asset based on the applicable IAS. This study uses a review literature model to find out accounting for Crypto-asset. The results of the study indicate that the most common treatment for Crypto-asset is as Intangible Asset and Inventory since the used of Crypto-asset until now mostly as investment and trading in contract futures.